Quality of Health Services in the City of Bandung - Putri, Dinda Jelita Handayana; Susilawati, Erna (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This paper explains the quality of health service delivery in Bandung City and its implications for patient satisfaction. Health services are a vital element of the public’s well-being, and the level of service quality significantly impacts patient satisfaction levels. The author uses a quantitative research method with a survey technique to obtain primary data from patients of health facilities in Bandung City. The research tool was a structured questionnaire based on the SERVQUAL model, which includes five main factors: tangibles, reliability, responsiveness, assurance, and empathy. The researchers reached people for the study using purposive sampling and then described the data with statistics and ran multiple linear regressions to find out how service quality dimensions affect patient satisfaction. According to the findings, patients in Bandung City generally perceived the quality of health services as good. Of all the five components, the caring aspect and the trustworthiness one are two areas that are strongest in patient satisfaction; thus, a highly positive patient experience is one where the doctor or health worker has shown care in a personal way, communicated well with the patient, and consistently provided service. The results from the regression also show a significant relationship between service quality and patient satisfaction. The present research would indicate that improving aspects of interpersonal communication, efforts to make waiting time as short as possible, and strengthening service management are the main ways to improve the quality of healthcare services.